Exploring the Acoustics of Ancient Open-Air Theatres - GIRÓN, Sara; ÁLVAREZ-CORBACHO, Ángel; ZAMARREÑO, Teófilo (Archives of Acoustics, 2020)
The theatres of Antiquity, Greek and Roman, constitute public buildings of the utmost importance in the history of Western culture and in universal cultural heritage. Many of these spaces are being used for their original function with or without only minor adaptations. If they are well preserved and/or restored, these performance buildings attract large audiences to representations of classical and contemporary plays, thereby serving the purpose for which they were built in the Ancient Age. These theatres bear witness to the existing relationship between architectural work, visual and acoustic experience, and dramatic art. Although the majority are located in the Mediterranean region, these structures were also built in the major cities of the ancient world in Europe, the Middle East, northern Africa, and beyond. This paper aims to summarise and critically review research published in the literature regarding their acoustic aspects, with particular emphasis on Roman theatres. These pieces of research emphasize the importance of the diffraction of sound in the tiers of the cavea and the good intelligibility for speech of the Greco-Roman theatre.